2008
DOI: 10.1245/s10434-008-0253-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive Surgery and Continuous Hyperthermic Peritoneal Perfusion in Patients with Mesothelioma and Peritoneal Carcinomatosis: Hemodynamic, Metabolic, and Anesthetic Considerations

Abstract: Cytoreductive surgery and continuous hyperthermic peritoneal perfusion (CHPP) involve the conduct of a complex surgical procedure and delivery of high-dose hyperthermic chemotherapy to the peritoneum. This therapeutic modality has been shown to benefit patients with peritoneal carcinomatosis resulting from gastrointestinal and ovarian tumors and mesothelioma. However, it is unknown whether the primary disease (mesothelioma versus peritoneal carcinomatosis) affects hemodynamic and metabolic perturbations during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 31 publications
5
67
0
1
Order By: Relevance
“…The operative time in this series was similar to reports in the literature [5]. Operative time and estimated blood loss were both increased in patients who developed complications, but this difference was not statistically different compared to uncomplicated patients.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The operative time in this series was similar to reports in the literature [5]. Operative time and estimated blood loss were both increased in patients who developed complications, but this difference was not statistically different compared to uncomplicated patients.…”
Section: Discussionsupporting
confidence: 85%
“…The mean patient age in Capone's study was 57 years, which is closer to the age of our patients that had complications [10]. Remarkably, the mean age in our study closely resembled that found in larger investigations of patient population with peritoneal carcinomatosis, likely reflecting the preponderance for this disease in this age group [1,4,5,11].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations